Georgia Architectural and Historic Properties Survey of Academy St., Rebecca, Turner County, Ga., March 1981. - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Academy St., Rebecca, Turner County, Ga., March 1981. 1 story rectangular clapboard Georgian plan with hipped and gabled roof. Gabled dormer. Smooth ionic columns support shed porch. Double hung sash windows with 1/1 lights and screened shutters. Transom over door. Interior chimney. Set on brick piers. Poor condition. Date of Construction: c. 1905. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough. Good example of Georgian plan house.
Georgia Architectural and Historic Properties Survey of Academy St., Rebecca, Turner County, Ga., March 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 56.8 MB (59,621,571 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Rebecca (Ga.); Turner County (Ga.)